Feeding standards for growing cattle* - UDEYBIR, UDEYBIR; MANDAL, A B (The Indian Journal of Animal Sciences, 2014)
The data of feeding trials (79), conducted on growing cattle in different institutes of India were collected. The data of body weights, gains and intakes were subjected to multiple regression analysis to derive the requirements of dry matter (DM), total digestible nutrients (TDN), crude protein (CP) and digestible crude protein (DCP) for maintenance and growth. The maintenance requirements ofDM and TDN in,growing cattle were 80.4 and 48.5 g, 85.3 and 42.7 g, 87.4 and 37.3 g, 78.1 and 40.1 g, and 71.8 and 38.9 g/W0 7S kg at 100, 150, 200, 250 and 300 kg live weight, respectively. The requirements for gain at corresponding live weight were 1.31 and 0.19g, 0.84 and 1.31 g, 0.57 and 1.72 g, 1.73 and 1.54 g, and 3.38 and 2.33 g, respectively. The maintenance requirements of CP and DCP were 9.50 and 5.95 g; 7.25 and 3.98 g; 6.51 and 3.76 g; 6.72 and 3.71 g; and 6.52 and 3.62g/w 075 kg and the corresponding values for gain were 0.33 and 0.21 g, 0.53 and 0.37 g, 0.63 and 0.39 g, 0.63 and 0.39 g, and 0.47 and 0.41 g at 100, 150, 200, 250 and 300 kg live weight, respectively. The regression equations and coefficients were significant (P